Organizational support for the potentially traumatic impact of video evidence of violent crime in the criminal justice system: ‘We’re almost making more victims’ - Birze, Arija (International review of victimology, 2023)
As graphic video evidence becomes a standard element in the investigation and prosecution of violent crime, criminal justice organizations must consider and address exposure to and impact of this potentially traumatizing workplace material for criminal justice professionals. Using a discovery-oriented qualitative design and a long-interview method of data collection, this study explores organizational responses to the exposure of criminal justice professionals to a growing volume of video evidence of violent crime. Repeated exposure to high-quality video evidence has the effect of placing criminal justice professionals in the midst of traumatic events, resulting in responses that are akin to trauma contagion. However, organizational awareness and the acceptance of trauma and support systems have not kept pace with the exponential rise in exposure, often being deployed when the person is no longer able to continue in their role. As a result, affected individuals may over-rely on equally affected colleagues for support, intensifying the cycle of trauma contagion. Organizational responses to reduce trauma contagion and the psychological burden on professionals working with video evidence of violent crime should occur at three levels: prevention through moderating exposure; preparation through creating a culture of awareness and acceptance; and intervention through systematic and formal supports.